Strategic formulation for the Al-Musayyib municipality directorate, according to use of the balanced scorecard for the years 2021-2025 - et. al., Rana Abd Ali Kazem Alijan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research problem revolves around the lack of a strategy for the municipality of Al-Musayyib that enables it to conduct its business in a complex environment, The importance of the research is evident in presenting a model for service organizations in general and municipalities in particular to evaluate their performance according to performance indicators for balanced scorecard perspectives and to use their results to formulate a strategy that enables them to adapt to the nature of their turbulent dynamic environment and raise their readiness to implement this strategy , The researcher chose the service sector for the current study and for the research community to be in the Al-Musayyib Municipality Directorate, which is one of the service institutions affiliated with the Ministry of Construction, Housing and Public Municipalities in Babylon Governorate , The researcher adopted the method of the intentional sample in selecting the research sample, which was represented by (15) director, assistant director, and division official in the searched directorate , Using the real data contained in the general directorate's budgets, final accounts, official records and annual reports during the years researched (2017-2019), performance measurement indicators, field coexistence, interviews and opinion poll forms for the research sample, and the questionnaire to evaluate the proposed strategy as tools for collecting information and data in the field side of the research , As well as using the (SWOT) matrix for the purpose of determining the environmental position of the investigated directorate , And( Bryson, 2011) model in determining the strategic issues of the directorate being the appropriate model for non-profit governmental institutions, The most prominent results that the researcher reached was that the performance of the Al-Musayyib municipality directorate for the years (2017-2019) was at an acceptable level, but with a negative performance gap, its percentage ranged between (40% and 41%) compared to the performance standards set by the researcher , As for the most prominent recommendations, the directorate should follow a therapeutic strategy in its work during the next five years and in line with what has been formulated of the strategic direction and the strategic issues of the investigated directorate.